2000
DOI: 10.1192/pb.24.8.302
|View full text |Cite
|
Sign up to set email alerts
|

A survey of training experiences and attitudes of higher specialist trainees in child and adolescent psychiatry

Abstract: Aims and MethodChanges in higher specialist training in the UK have led to a revision of training guidelines in child and adolescent psychiatry. This survey studies trainees' experiences and attitudes in the light of these changes. A questionnaire covering training attitudes and experiences was distributed to all higher specialist trainees in child and adolescent psychiatry via their programme directors.ResultsEighty-eight per cent of trainees responded. Although most training experiences are well provided, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…Other studies show that only half of SpRs in psychiatry had ever managed to secure a publication (Smart & Cottrell, 2000;Allsopp et al, 2002). These surveys also highlighted difficulties such as lack of protected time, inadequate supervision and poor resources (such as access to computers and software).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies show that only half of SpRs in psychiatry had ever managed to secure a publication (Smart & Cottrell, 2000;Allsopp et al, 2002). These surveys also highlighted difficulties such as lack of protected time, inadequate supervision and poor resources (such as access to computers and software).…”
Section: Discussionmentioning
confidence: 99%
“…A study previously carried out showed that 31% of higher trainees in child and adolescent psychiatry in the UK had no formal training in research methods and a significant number of trainees were undertaking research without resultant publications. 8 It follows, therefore, that access to appropriate research supervision and training in statistical methods needs assessment to ensure that the maximum benefit of this valuable time is obtained. Making the most economic use of senior registrars' time is also highlighted by the high numbers of senior registrars who report completing administrative duties such as filing, sending out appointments and occasionally typing.…”
Section: Discussionmentioning
confidence: 99%
“…Only half of the SpRs in psychiatry have ever managed to secure a publication (Smart & Cottrell, 2000). Recent surveys have suggested that problems with lack of experience, resources and supervision may be a reason for this (Petrie et al, 2003).…”
Section: Higher Specialist Trainingmentioning
confidence: 99%